SOVEREIGNTY, NATIONAL INTEREST AND SECURITY IN BILATERAL INVESTMENT TREATIES OF MALAYSIA (Journal of International Studies, 2020)
The bilateral investment treaties (BITs) have continued to play a significant role in regulating foreign direct investments (FDI) in many countries. Member countries of the World Trade Organization (WTO), including Malaysia, have signed BITs to facilitate trade among nations. Malaysia’s FDI laws and BITs were established to protect foreign investors, however, neither legislation had provided specific provisions on the protection of sovereignty, national interest and security. This study was conducted to address the question; to what extent are sovereignty, national interest and security protected through BITs upon the introduction of FDI into Malaysia? This study employed a non-doctrinal socio-legal research methodology, whereby the authors analyzed 15 BITs between Malaysia and other countries to explore the provisions that pertains to the protection of sovereignty, national interest and security in Malaysia. The findings conclude that the existing Malaysian BITs contain provisions to promote and protect foreign investments, however, lacked the necessary provisions on the protection of sovereignty, national interest and security. Therefore, the government should reconsider these important factors when signing future BITs.